2015
DOI: 10.1590/s0100-736x2015000400002
|View full text |Cite
|
Sign up to set email alerts
|

Perdas econômicas ocasionadas por lesões em carcaças de bovinos abatidos em matadouro-frigorífico do norte de Mato Grosso

Abstract: RESUMO.-Este estudo teve o objetivo de avaliar as perdas econômicas decorrentes de lesões de transporte e manejo pré-abate em carcaças de bovinos abatidos em matadouro-frigorífico inspecionado na região norte do Estado de Mato Grosso/MT, Brasil. De um total de 1.021 animais avaliados identificou-se que 433(42,4%) apresentavam carcaças com lesões relacionadas ao transporte e manejo pré-abate. A frequência de lesões encontradas evidenciou uma diferença (P<0,05)de acordo com o tempo de transporte, em que, com o t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…A couple of studies have addressed unhealthy animals and outbreaks of disease, by assessing the economic losses due to diseases in cattle, particularly parasitic diseases (Grisi et al , 2014; Rodríguez-Vivas et al , 2017). Other studies have focussed on the inadequacy of the handling and transportation infrastructures leading to cattle injuries and bruises at the farm and during the shipping, transporting of live animals and pre-slaughter handling (Polizel Neto et al , 2015; Mendonça et al , 2019), with Miranda-de la Lama et al (2014) defending the need to improve logistics that prioritize animal welfare and to convince the meat industry and consumers that the ethical value of a product has growing economic importance and can be a business opportunity. Mena et al (2014) studied the causes of FLW across the food networks of different food products in different UK SCs and concluded that the causes fell into two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of studies have addressed unhealthy animals and outbreaks of disease, by assessing the economic losses due to diseases in cattle, particularly parasitic diseases (Grisi et al , 2014; Rodríguez-Vivas et al , 2017). Other studies have focussed on the inadequacy of the handling and transportation infrastructures leading to cattle injuries and bruises at the farm and during the shipping, transporting of live animals and pre-slaughter handling (Polizel Neto et al , 2015; Mendonça et al , 2019), with Miranda-de la Lama et al (2014) defending the need to improve logistics that prioritize animal welfare and to convince the meat industry and consumers that the ethical value of a product has growing economic importance and can be a business opportunity. Mena et al (2014) studied the causes of FLW across the food networks of different food products in different UK SCs and concluded that the causes fell into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern in the Brazilian beef SC lies in the injuries sustained by cattle during shipping, the transportation of live animals and pre-slaughter handling. The frequency of the injuries varies significantly with the shipping times and the consequent annual economic losses in a mid-sized slaughterhouse may exceed US$ 63,000 (Polizel Neto et al , 2015). Notwithstanding, in Brazil, beef wastage also exists among the householders due mainly to lifestyle and cultural reasons (Bastos, 2018).…”
Section: The Brazilian Beef Scmentioning
confidence: 99%
“…Para identificar, quantificar e pesar as contusões, primeiramente dividiu a carcaça do animal em partes que foram observadas facilitando o preenchimento do formulário. A divisão foi realizada com base nos estudos feitos por Polizel Neto et al (2015), separando a carcaça por região de 1 à 5, sendo 1-Pescoço, 2-Dianteiro (paleta), 3-Costelas, 4-Região do Lombo e 5-Traseiro, tal método facilitou o preenchimento referente ao local da lesão e quantidade de lesões observadas por região.…”
Section: Methodsunclassified
“…Os prejuízos econômicos causados por um manejo pré-abate ineficiente, são um reflexo das mudanças necessárias por parte dos produtores, os quais na atualidade são os mais afetados devido à desvalorização de seu produto. Polizel Neto et al (2015), ao investigar as perdas econômicas decorrentes de lesões de transporte e manejo préabate em 1.021 carcaças de bovinos abatidos no matadouro/frigorífico na região norte de Mato Grosso -MT, Brasil, observaram que 433 (42,4%) apresentavam carcaças com lesões, encontrando perda de 115,76 Kg para o total de animais estudados, estimando que um matadourofrigorífico de porte médio acumula uma perda anual superior a 200 mil reais com lesões em carcaças bovinas decorrentes do transporte. Mendonça et al (2016), ao avaliar o grupo genético e presença de chifres em contusões e perdas econômicas em carcaças bovinas, observaram que a maior perda ocorreu no grupo dos zebuínos, totalizando 1,21 Kg/carcaça (R$ 15,48/animal).…”
Section: Aspectos Da Relação Entre Fatores E Seus Impactosunclassified